Habitat associations of juvenile Atlantic cod (Gadus morhua L.) and sympatric demersal fish communities within shallow inshore nursery grounds. (5th December 2022) - Dunlop, Katherine; Staby, Arved; van der Meeren, Terje; Keeley, Nigel; Olsen, Esben M.; Bannister, Raymond; Skjæraasen, Jon Egil
Abstract: Resolving the relationship between demersal fish and sublittoral biotic habitats and substrates is a key element in the protection of important nursery grounds for strengthening fish recruitment. In Norway, coastal Atlantic cod ( Gadus morhua L.) is a commercially and culturally important demersal fish for Norwegian coastal communities, and in recent decades the stock has declined to such an extent that a plan to rebuild the stock to biologically safe limits has been implemented. Yet, little is known about the specific biotic and abiotic habitat associations of the early-life stages of coastal cod, which is important for the management and protection of the species. The same shallow, sublittoral zones are inhabited by juveniles and adults of other commercial demersal gadoids and wrasses. This study presents novel findings on associations between juvenile coastal cod and other demersal fish species with seafloor substrates and biological habitats, inferred from five years of extensive fyke net surveys. Newly settled 0-group cod were typically associated with eel grass and red algae biotic habitats on sand and shell sand substrates. However, there was an ontogenic habitat shift amongst one year old (1-group) individuals that became more ubiquitous with their biotic habitat or substrate type choices. The juvenile gadoids saithe ( Pollachius virens ) and pollack ( Pollachius pollachius ), were most associated with hard bottom dominated sites with saithe being more abundant at exposed sites, compared to pollack. Goldsinny wrasse ( Ctenolabrus rupestris ) and corkwing wrasse ( Symphodus melops ) appeared to favor sugar kelp forests and red algae. Overall, the study identifies the specific sublittoral biotic habitats and substrates important to different early life stages of juvenile coastal cod and other commercially important demersal fish, providing critical information needed for identifying candidate coastal habitats for protection. Highlights: Newly settled 0-year Atlantic cod prefer red algae habitats as well as eelgrass. Atlantic cod juveniles over 1 year do not show specific habitat associations. Red algal habitats and sugar kelp forests favored by wrasse. Saithe associated with exposed bedrock sites while more pollack were in mixed substrates in more sheltered areas. Knowledge of specific sublittoral habitat associations to improve cod and demersal fish management.